2017
DOI: 10.1111/cea.12877
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia causes IL‐8 secretion, Charcot Leyden crystal formation, and suppression of corticosteroid‐induced apoptosis in human eosinophils

Abstract: Summary Background Inflamed environments are typically hypercellular, rich in pro‐inflammatory cytokines, and profoundly hypoxic. While the effects of hypoxia on neutrophil longevity and function have been widely studied, little is known about the consequences of this stimulus on eosinophils. Objective We sought to investigate the effects of hypoxia on several key aspects of eosinophil biology, namely secretion, survival, and their sensitivity to glucocorticosteroids (GCS), agents that normally induce eosinoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…Inflamed lesions are often severely hypoxic due to increased cellular oxygen demand and reduced oxygen availability ( 38 – 40 ). Hypoxia is a potent pro-inflammatory stimulus for both neutrophils and eosinophils, contributing to an anti-apoptotic and a hyper-secretory profile in both cell types (notably enhanced release of neutrophil elastase and myeloperoxidase from neutrophils and Charcot–Leyden crystal/Galectin-10 production by eosinophils) ( 22 , 40 ). In our study, hypoxia profoundly suppressed mitochondrial oxidative phosphorylation in eosinophils, indicative of a metabolic pathway shift from oxidative phosphorylation to glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Inflamed lesions are often severely hypoxic due to increased cellular oxygen demand and reduced oxygen availability ( 38 – 40 ). Hypoxia is a potent pro-inflammatory stimulus for both neutrophils and eosinophils, contributing to an anti-apoptotic and a hyper-secretory profile in both cell types (notably enhanced release of neutrophil elastase and myeloperoxidase from neutrophils and Charcot–Leyden crystal/Galectin-10 production by eosinophils) ( 22 , 40 ). In our study, hypoxia profoundly suppressed mitochondrial oxidative phosphorylation in eosinophils, indicative of a metabolic pathway shift from oxidative phosphorylation to glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…EOS and tumor associated macrophages accumulated in the hypoxic and/or necrotic areas of mouse subcutaneous B16F10 melanoma, and this process was associated with EOS degranulation (22). These particles of EOS degranulation contain VEGF and other angiogenic factors, which may promote tumor angiogenesis in the hypoxic areas (38,39). In addition, EOS promotes angiogenesis in local cancer lesion by releasing a large number of vasoactive leukotrienes (40).…”
Section: Discussionmentioning
confidence: 99%
“…In eosinophils, Porter et al showed that hypoxia increased the release of IL-8 but attenuated that of eosinophil-derived neurotoxin, with no change in mRNA levels even at 24 h [67]. The phenomenon of "piecemeal degranulation" has been described for both mast cells and eosinophils, whereby release of selected proteins or cytokines occurs via vesicle or vesiculo-tubular sequential emptying of granules [68]; it is possible that hypoxia may be able to access or modify this system of protein secretion.…”
Section: Effect Of Hypoxia On Protein Secretion From Non-neutrophilsmentioning
confidence: 99%
“…How hypoxia might modulate PI3Kγ signalling in a HIF-independent fashion remains unclear. It is conceivable that hypoxic reorganisation of the actin cytoskeleton facilitates access of PI3Kγ to its phospholipid substrate; cytoskeletal disruption has been linked to enhanced neutrophil degranulation [85], and hypoxia has been shown to promote focal actin polymerisation in neutrophils, forming cap-like structures [24], similar to the actin reorganisation seen in hypoxic eosinophils [67]. Another possibility is that hypoxia is able to regulate PI3K expression.…”
Section: Pi3k Signalling Is Involved In Neutrophil Degranulation Undementioning
confidence: 99%